Preoperative Activity Level an Indicator of Postoperative Functional Outcomes with a Contemporary Revision Total Knee System - Auran, Richard L.; Ashby, Samuel L.; Hitt, Kirby D.; Jacofsky, David J. (The Journal of Knee Surgery, 2022)
As the population requiring revision total knee arthroplasty (rTKA) grows, varying preoperative conditions may need to be considered when attempting to predict postoperative outcomes. Considering preoperative activity levels may help manage the expectations of patients. The purpose of this study was to analyze the outcomes of low- and high-activity subgroups of patients receiving a contemporary rTKA. One hundred and eighty-one rTKA patients enrolled in a prospective multicenter study were evaluated over a minimum follow-up of 2 years postoperatively. Patients were divided into two groups based on the preoperative activity level using the Lower Extremity Activity Scale. Patients scoring between 1 and 7 were classified as “Low Activity” (LA; N = 105) and patients scoring 8 to 18 were classified as “High Activity” (HA; N = 76). Clinical outcomes were evaluated, with an additional quality-of-life analysis completed utilizing SF-6D (6-dimension short form) scores obtained through a method described by Brazier et al and analyzed for effect size. There were no significant differences in age or body mass index between the groups. Postoperative improvement in both groups were similar in the Knee Society score (KSS), but the LA group showed larger increases in the KSS functional assessment at 6 months (16.2) and 2 years (34.8). There was a statistically significant effect (0.96, p = 0.0006) seen in the LA group at 1 year, in conjunction with a higher SF-6D outcome. The current study population displayed significant improvement in functional patient outcomes following rTKA regardless of preoperative activity level and function. Patients with lower preoperative activity levels demonstrated greater cumulative functional and quality-of-life improvements. This suggests that a lower preoperative activity level may be related to a poorly functioning knee and that rTKA has the potential to improve overall activity levels and function. Low preoperative function should not disqualify patients for rTKA.
Keywords: revision total knee arthroplasty; functional outcomes; activity levels